2018
DOI: 10.1021/acs.jpcc.8b07391
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Activation in Oxidative Coupling of Methane on Calcium Oxide

Abstract: A pulsed isotope exchange technique was applied to study the oxygen scrambling activity of polycrystalline calcium oxide under temperatures and pressures relevant for the oxidative coupling of methane (OCM). Oxygen exchange was observed above 400 °C. The onset was attributed to the removal of impurities on the catalyst surface. By trapping impurities in the gas feed, the scrambling could already be observed at room temperature. An activation energy of 80 kJ/mol was determined for the oxygen scrambling of O2 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
(115 reference statements)
1
15
0
Order By: Relevance
“…A thin layer of the stable carbonate species could be present at the surface during OCM. Recent temperature-programmed OCM reaction studies of Thum et al on CaO showed that carbonate phases can be present at reaction conditions and start to decompose at ~750 °C [ 31]. Also IR spectra obtained after OCM for materials lying on the top of volcano (Rb2CO3-Sm2O3) indicate the presence of small amounts of carbonates after OCM exposure (Fig.…”
Section: Discussion and Mechanistic Interpretationmentioning
confidence: 86%
See 1 more Smart Citation
“…A thin layer of the stable carbonate species could be present at the surface during OCM. Recent temperature-programmed OCM reaction studies of Thum et al on CaO showed that carbonate phases can be present at reaction conditions and start to decompose at ~750 °C [ 31]. Also IR spectra obtained after OCM for materials lying on the top of volcano (Rb2CO3-Sm2O3) indicate the presence of small amounts of carbonates after OCM exposure (Fig.…”
Section: Discussion and Mechanistic Interpretationmentioning
confidence: 86%
“…So far, neither stability nor reactivity of supported carbonates can be comprehensively assessed from either literature data or ab initio calculations. As a matter of fact, the functions that have been attributed to carbonates in literature range from deactivation of catalysts [30,31] to promotion of catalytic activity [32]. The OCM performance data reported in literature were often obtained at the reaction conditions that varied significantly between different catalysts, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Research has long aimed to evaluate the potential feasibility of recycling OCM produced CO 2 into the catalytic OCM reactor. As discussed in the previous section, the co-feeding of CO 2 with CH 4 and O 2 mixtures over catalytic OCM reactors has been demonstrated to result in significantly lower methane conversions and ethene yields, a fact usually associated with the competitive adsorption of CO 2 and O 2 on catalyst active sites [92,102,147,148]. However, it has also been suggested that the co-feeding of CO 2 can play a role in improving catalyst stability [147] and even present a positive impact on ethene yield, either through its interaction with the catalyst surface [28] or by enabling changes in CH 4 and O 2 diffusivities when used as a diluent, which could create local environments of higher CH 4 /O 2 molar ratios within the catalyst bed [149].…”
Section: Co-feeding Of Comentioning
confidence: 96%
“…5,6 Related transformation processes are additionally affected by by-products and products that form in the course of catalytic reactions. 7 A prominent and ubiquitous component with a substantial impact on oxide nanoparticle stability is water. 8,9 For this reason, the formation and readsorption of water during catalysis [10][11][12][13][14] has remained a key research topic in a variety of research fields that…”
Section: Introductionmentioning
confidence: 99%
“…Here, water is detrimental not only as it promotes catalyst coarsening but also as catalyst deactivation may result from the hydroxylation of the particle surfaces. 7 As a consequence, high temperatures are necessary process parameters to eliminate surface water from the catalyst surface during the catalytic reaction. 5,17 Another major issue related to the OCM reaction is the generally low selectivity of the catalysts.…”
Section: Introductionmentioning
confidence: 99%